Why Do We Continue Doing Science? - Leach, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In this paper I speak from both a scientific and religious perspective. From this dual perspective I question the motivations that drive us to continue in the effort of doing scientific work. I ask the why and the wherefore of scientific work. To answer this question: What drives us to continue doing Science? I raise a preliminary question: What do we mean when we say ‘Science’? After briefly describing how the language of Modern Science has evolved in the last centuries, I distinguish between the knowledge that can be expressed by the formal languages of mathematics and the more personal and internal knowledge that can only be expressed by other languages that I call languages of symbol. Finally I propose positive and religious values that move us to continue doing science, while, together with more critical voices, also show the relativity of scientific work